Neoadjuvant therapy for pMMR/MSS locally advanced rectal cancer in the immunotherapy era: current landscape and future perspectives - Farooq, Benish; Li, Xingyu; Xiao, Sa; Liu, Xiaojun (Frontiers in Oncology, 2025)
Numerous clinical studies indicate that neoadjuvant chemoradiotherapy (NCRT) with immunotherapy can significantly increase pathological complete response (pCR) and clinical complete response (cCR) rates to over 30-60%, substantially higher than the 15-20% observed with conventional NCRT. This allows more patients to become eligible for a Watch-and-Wait (WW) strategy, successfully preserving organ function. Several phase III randomized controlled trials (RCTs) are currently underway. The combination of NCRT and immunotherapy holds promise for breaking the therapeutic impasse in proficient mismatch repair/microsatellite stability (pMMR/MSS) rectal cancer, markedly enhancing tumor regression and the potential for organ preservation. However, challenges remain for NCRT combined with immunotherapy in this population. First of all, there is an unmet need to identify predictive biomarkers for treatment response in pMMR/MSS rectal cancer. Next, treatment protocols require further optimization, specifically in determining the best radiotherapy fractionation schedule, its sequencing with immunotherapy, and the radiotherapy target volume. Otherwise, the phenomenon of “pseudo-residual disease” complicates traditional radiological assessment of cCR and must be overcome. Furthermore, the long-term survival benefits of combining radiotherapy with immunotherapy need further confirmation. This review provided a comprehensive and in-depth view of immunotherapy-based NCRT (iNCRT) in patients with pMMR/MSS rectal cancer and discuss the new opportunities and challenges this strategy presents for achieving organ preservation.